Manuel Sánchez Asensio (1860-1919) a través de los periódicos que fundó y dirigió - Sánchez Pérez, Carlos Manuel (Documentación de las Ciencias de la Información, 2007)
The life and work of famed journalist Manuel Sánchez Asensio, founder of fourteen newspapers and the author of 15,000 articles, are presented. The diverse publications, their goals, characteristics and contents are covered. The philosophy and thinking of Sánchez Asensio expressed in his very first articles published in the magazine La Tesis until his last texts appearing in the newspaper El Siglo Futuro, are analyzed in depth.